Sources of Administrative Law in Vietnam: A Comparative Framework for Legal Harmonization - Vu Minh Chau (IJOLARES: Indonesian Journal of Law Research, 2025)
Vietnam's shift from a centrally planned economy to a market-oriented system under the Đổi Mới reforms has exposed significant challenges in its administrative law system. Traditionally based on a civil law model that prioritizes hierarchical legal documents, the system is now increasingly influenced by judicial decisions, international treaties, and informal administrative practices that are not formally recognized as legal sources. This study uses a comparative legal method, analyzing administrative law frameworks in France and the United Kingdom, to evaluate how Vietnam’s legal system addresses these emerging complexities. The research draws on legal texts, court rulings, and administrative guidelines from all three countries to assess coordination mechanisms and identify governance gaps. For instance, in Vietnam, the absence of legal recognition for judicial precedents leads to inconsistent application of laws across provinces. To address these issues, the study proposes a hybrid harmonization model: integrating judicial precedents into the legal hierarchy, defining general principles of administrative law, and establishing institutions responsible for legal coherence. These reforms aim to improve administrative accountability and support Vietnam’s legal modernization in line with its ongoing economic integration.